Catalyst component for ethylene polymerization reaction as well as preparation method and application of catalyst component

By reacting with components such as magnesium and titanium compounds using hexagonal mesoporous material support, an efficient ethylene polymerization catalyst was prepared, which solved the problem of low activity of the existing catalyst and achieved the effect of high catalytic activity and high bulk density.

CN119841983AActive Publication Date: 2025-04-18CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311334286.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-18
Estimated Expiration
2043-10-16

AI Technical Summary

Technical Problem

The existing ethylene polymerization catalysts have low activity, and the support surface properties and pore structure limit the payload of the active components, resulting in poor catalytic activity.

Method used

Hexagonal mesoporous material support is prepared by mixing contact and crystallization of template agent, potassium sulfate, acid agent and ethyl orthosilicate, and contact reaction with magnesium compounds, titanium oxide compounds, alcohol ether compounds and halogenation reagents to form efficient catalyst components.

Benefits of technology

The catalytic activity of the catalyst is improved, the bulk density of the polymer is enhanced, the process flow is simplified, the waste slag generation is reduced, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841983A_ABST
    Figure CN119841983A_ABST
Patent Text Reader

Abstract

The invention relates to the field of catalysts for preparing olefin polymers, in particular to a catalyst component for an ethylene polymerization reaction, a preparation method of the catalyst component, a catalyst for the ethylene polymerization reaction and application of the catalyst. The catalyst component comprises a reaction product of the following raw materials: at least one carrier, at least one magnesium compound, at least one oxygen-containing titanium compound, at least one alcohol ether compound, at least one ether compound and at least one halogenation reagent, the carrier has a cubic cage-shaped pore channel structure, the crystal structure has a cubic-core Im3m structure, the average pore size is 4-15 nm, the specific surface area is 450-550 m < 2 > / g, the pore volume is 0.5-1.5 mL / g, and the average particle size is 0.5-10 [mu] m. The magnesium-titanium compound dissolving solution is good in solubility and transparency and high in catalytic activity, and powder obtained through polymerization is high in stacking density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalysts for preparing olefin polymers, in particular to a catalyst component for ethylene polymerization reaction and a preparation method thereof, a catalyst for ethylene polymerization reaction and an application thereof. Background Art

[0002] With the development of ethylene polymerization process, the catalyst preparation technology matched with the polymerization process is also constantly improving. At present, the Ziegler-Natta catalyst system of Ti / Mg complex still occupies a dominant position in the industrial production of polyethylene. The polymerization activity, hydrogen adjustment sensitivity, particle morphology of the catalyst, and the bulk density of polymer powder are all very important parameters in industrial production. The improvement of catalyst activity and productivity can improve economic benefits. The increase of polymer bulk density in industry allows longer catalyst residence time, which is conducive to increasing reactor output and achieving better reactor operability. The catalyst affects the bulk density, fluidity, particle adhesion and other parameters of polymer powder. The polymer replicates the morphology of the catalyst. The poor catalyst morphology may cause the polymer morphology to deteriorate, which may cause scaling or flaking in industrial equipment. Therefore, the industry needs a catalyst with good morphology control, required particle size and morphology, narrow distribution, high bulk density and low adhesion.

[0003] In order to obtain a good particle morphology, technicians often use a loading method to prepare catalysts, and the catalyst active components are impregnated on a particle carrier material, such as a porous inorganic carrier material silica or an organic particle carrier material. For example, US4293673, US4303771, US4302565, US4302566, and EP0835887A2 disclose that magnesium compounds and titanium compounds are loaded on an inorganic carrier to prepare a catalyst. The morphology of the carrier determines the morphology of the final catalyst. This preparation method has high requirements on the morphology and surface properties of the carrier, resulting in an increase in the catalyst preparation cost. In addition, the disadvantage of the loaded catalyst is that the impregnation step may cause uneven loading of the active components on the carrier surface. At the same time, due to the limitation of the specific surface area of ​​the carrier, the loading amount and distribution of the active center are limited, thereby limiting the improvement of the catalyst activity.

[0004] CN1085915A discloses a method for preparing a Ziegler-Natta catalyst system. In tetrahydrofuran, titanium tetrachloride is reduced by magnesium metal to obtain a tetrahydrofuran solution of TiCl3, and then magnesium chloride is dissolved in tetrahydrofuran, the two solutions are fully mixed, unreacted magnesium and undissolved magnesium chloride are filtered out, the filtered solution is fully mixed with silica gel, and then spray-dried to obtain dispersed particles of the catalyst, which has high activity and high titanium content. The preparation method requires a filtering step, produces more waste residue, and increases the post-processing steps and costs.

[0005] Therefore, it is necessary to provide a catalyst suitable for ethylene polymerization process, which not only needs to have high catalytic activity, but also should have good catalyst particle morphology and polymer particle morphology, and high polymer bulk density. Summary of the invention

[0006] In order to solve the problems existing in the above prior art, the present invention proposes a catalyst component for ethylene polymerization reaction and a preparation method thereof, a catalyst for ethylene polymerization reaction and its application. The purpose of the present invention is to overcome the defects that the existing polyolefin catalyst is limited by the surface properties, pore structure and solubility of the components to be loaded on the carrier, the effective loading amount of the catalyst active components on the carrier is low, and then the catalytic activity of the loaded polyolefin catalyst prepared by the existing loaded polyolefin catalyst carrier is poor, and a method for preparing a polyolefin catalyst, a polyolefin catalyst prepared by the above method, the application of the polyolefin catalyst prepared by the above method in the polymerization reaction of olefin monomers and the polyolefin prepared by the method are provided. The present invention has a high catalytic activity when used for ethylene homopolymerization or copolymerization, and the prepared polymer powder has a high bulk density. The active center mother liquor of the present invention does not need to be filtered before the mixed reaction with the carrier, the process is simple and environmentally friendly.

[0007] The first aspect of the present invention is to provide a catalyst component comprising the reaction product of at least one support, at least one magnesium compound, at least one oxygen-containing titanium compound, at least one alcohol ether compound, at least one ether compound and at least one halogenating agent;

[0008] The carrier is a hexagonal mesoporous material carrier, which has a cubic cage-like pore structure, a crystal structure with a cubic center Im3m structure, an average pore diameter of 4-15nm, and a specific surface area of ​​450-550m 2 / g, the pore volume is 0.5-1.5mL / g, and the average particle size is 0.5-10μm.

[0009] According to a preferred technical solution of the present invention, the carrier is prepared by the following method:

[0010] (a) mixing and contacting a template, potassium sulfate, an acid agent and tetraethyl orthosilicate, and crystallizing and filtering the obtained mixture to obtain a raw powder of a hexagonal mesoporous material;

[0011] (b) subjecting the raw powder of the hexagonal mesoporous material to a template release treatment, a heat activation treatment and a ball milling treatment in sequence to obtain a hexagonal mesoporous material carrier.

[0012] According to the present invention, in step (a), the process of preparing the hexagonal mesoporous material raw powder with a cubic center Im3m structure may include: mixing and contacting a template, potassium sulfate, an acid agent and tetraethyl orthosilicate, and crystallizing and filtering the obtained mixture. The order of the mixed contact is not particularly limited, and the template, potassium sulfate, an acid agent and tetraethyl orthosilicate may be mixed at the same time, or any two or three may be mixed, and then other components are added and mixed evenly. According to a preferred embodiment, the template, potassium sulfate and an acid agent are first mixed evenly, and then tetraethyl orthosilicate is added and mixed evenly.

[0013] In the present invention, the amount of the template, potassium sulfate and tetraethyl orthosilicate can vary within a wide range, for example, the molar ratio of the template, potassium sulfate and tetraethyl orthosilicate can be 1:100-800:20-200, preferably 1:150-700:80-180, more preferably 1:200-400:100-150.

[0014] In the present invention, the template agent may be any conventional template agent in the art. For example, the template agent may be a triblock copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene, which may be prepared by methods known to those skilled in the art, or may be commercially available, for example, from Fuka Company under the trade name Synperonic F108, with a molecular formula of EO 132 PO 60 EO 132 , the average molecular weight Mn = 14600. The molar number of polyoxyethylene-polyoxypropylene-polyoxyethylene is calculated based on the average molecular weight of polyoxyethylene-polyoxypropylene-polyoxyethylene.

[0015] In the present invention, the acid agent may be various acidic aqueous solutions commonly used in the art, for example, it may be at least one aqueous solution of hydrochloric acid, sulfuric acid, nitric acid and hydrobromic acid, preferably a hydrochloric acid aqueous solution.

[0016] The amount of the acid agent used is not particularly limited and can vary within a wide range, preferably making the pH value of the mixture 1-7.

[0017] The present invention has no particular limitation on the conditions of the mixed contact, for example, the mixed contact conditions may include: a temperature of 25-60° C., a time of 10-240 min, and a pH value of 1-7. In order to facilitate uniform mixing of the various substances, according to a preferred embodiment of the present invention, the mixed contact is carried out under stirring conditions.

[0018] According to a preferred embodiment of the present invention, the process of mixing and contacting the template, potassium sulfate, acid and tetraethyl orthosilicate comprises: adding the template triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene F108 to an aqueous solution of hydrochloric acid, in a molar feed ratio of triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene F108: potassium sulfate: water: hydrogen chloride = 1:200-400:10000-30000:100-900, stirring at a temperature of 25-60°C until dissolved, and then adding tetraethyl orthosilicate to the above-mentioned resulting solution, the amount of the tetraethyl orthosilicate used is in a molar feed ratio of triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene F108: tetraethyl orthosilicate = 1:100-150, and stirring at a temperature of 25-60°C for 10-240 minutes.

[0019] In the present invention, the crystallization conditions are not particularly limited, for example, the crystallization conditions may include: a temperature of 25-60°C, preferably 30-55°C; a time of 10-72h, preferably 10-40h. According to a preferred embodiment, the crystallization is performed by a hydrothermal crystallization method.

[0020] In the present invention, the process of obtaining the raw powder of hexagonal mesoporous material having a cube-centered Im3m structure by filtering may include: after filtering, repeatedly washing with deionized water (the number of washing times may be 2-10), and then performing suction filtration.

[0021] According to the present invention, in step (b), the method for removing the template is generally a calcination method. The conditions for removing the template can be selected conventionally in the art, for example, the process of removing the template may include: calcining the hexagonal mesoporous material raw powder at 300-600°C for 8-20h.

[0022] According to the present invention, in step (b), in order to remove hydroxyl groups and residual moisture of the hexagonal mesoporous material carrier, thermal activation treatment is required before the hexagonal mesoporous material carrier is loaded with magnesium and / or titanium active components. The conditions of the thermal activation treatment may include: in the presence of nitrogen, calcining the hexagonal mesoporous material carrier at a temperature of 300-900°C for 7-10h.

[0023] According to the present invention, in step (b), the specific operation method and conditions of the ball milling treatment are based on not destroying or substantially not destroying the pore structure of the hexagonal mesoporous material having a cube-centered Im3m structure. Those skilled in the art can select various suitable conditions to implement the present invention according to the above principles. Specifically, the ball milling treatment can be carried out in a ball mill, wherein the diameter of the grinding balls in the ball mill can be 2-3 mm; the number of grinding balls can be reasonably selected according to the size of the ball mill jar, and for a ball mill jar of 50-150 mL in size, 20-80 grinding balls can usually be used; the material of the grinding balls can be agate, polytetrafluoroethylene, etc., preferably agate. The conditions of the ball milling treatment include: the rotation speed of the grinding balls is 300-500r / min, and / or, the temperature in the ball mill jar is 15-100°C, and / or, the ball milling time is 0.1-100h. Preferably, the ball milling conditions include: the rotation speed of the grinding balls can be 300-500 r / min, the temperature in the ball milling jar can be 15-100° C., and the ball milling time can be 0.1-100 hours. Preferably, in step (b), the ball milling conditions are such that the average particle diameter of the hexagonal mesoporous material carrier obtained by ball milling is 0.5-10 μm.

[0024] According to the present invention, the polyolefin catalyst comprises a carrier and a magnesium component and / or a titanium component loaded on the carrier, wherein the carrier is a hexagonal mesoporous material carrier, the hexagonal mesoporous material carrier has a cubic cage-like pore structure, the crystal structure of the hexagonal mesoporous material has a cubic-centered Im3m structure, the average pore size of the hexagonal mesoporous material is 4-15nm, and the specific surface area is 450-550m 2 / g, the pore volume is 0.5-1.5mL / g, and the average particle size is 0.5-10μm.

[0025] According to the present invention, in the polyolefin catalyst, since the hexagonal mesoporous material carrier obtained by the method of the present invention has a special cube-centered crystal structure, its crystal structure has a cube-centered Im3m structure, and the cubic cage-like pore structure unique to the hexagonal mesoporous material, combined with its narrow pore size distribution and uniform pore distribution, is conducive to the good dispersion of magnesium and / or titanium active components on the carrier surface, so that the prepared polyolefin catalyst has both good dispersion of metal active components and high loading capacity, ensuring that the loaded catalyst made using the hexagonal mesoporous material as a carrier has better catalytic activity in olefin monomer polymerization reactions, and significantly improves the conversion rate of reaction raw materials.

[0026] According to the present invention, the average particle size of the hexagonal mesoporous material is measured by a laser particle size distribution instrument, and the specific surface area, pore volume and average pore size are measured according to a nitrogen adsorption method. In the present invention, the particle size refers to the particle size of the raw material particles. When the raw material particles are spheres, the particle size is expressed by the diameter of the sphere, when the raw material particles are cubes, the particle size is expressed by the side length of the cube, and when the raw material particles are irregular in shape, the particle size is expressed by the mesh size of the sieve that can just sieve out the raw material particles.

[0027] In a preferred embodiment, the average pore size of the hexagonal mesoporous material is 4-12 nm, such as 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm and 12 nm, and any average pore size between any two average pore sizes, and the specific surface area is 480-520 m 2 / g, the pore volume is 0.5-1mL / g, and the average particle size is 0.8-8μm, which can ensure that the hexagonal mesoporous material has the advantages of larger pore size, larger pore volume, and larger specific surface area, which is more conducive to the good dispersion of magnesium and / or titanium active components on the surface of the hexagonal mesoporous material, and further ensure that the polyolefin catalyst prepared therefrom has excellent catalytic performance, thereby obtaining beneficial effects such as high olefin monomer conversion rate and high polymer bulk density and excellent fluidity.

[0028] According to a preferred technical solution of the present invention, the magnesium compound is of the general formula (I) Mg(OR 1 ) m Cl 2-m As shown, R 1 C2-C 20 Saturated or unsaturated straight or branched chain hydrocarbon group, or C3-C 20 Saturated or unsaturated cyclic hydrocarbon group, R 1 Preferably C2-C 10 0≤m≤2; According to the catalyst component provided by the present invention, preferably, in the general formula (I), R 1 C2-C 10 the magnesium compound is preferably selected from an alkoxy magnesium compound and / or magnesium chloride, more preferably at least one selected from diethoxy magnesium, dipropoxy magnesium, dibutoxy magnesium, dioctyloxy magnesium and magnesium dichloride.

[0029] According to the preferred technical solution of the present invention, the oxygen-containing titanium compound is of the general formula (II) Ti(OR 2 ) n Cl 4-n As shown, R 2 C2-C 20 Saturated or unsaturated straight or branched chain hydrocarbon group, or C3-C 20Saturated or unsaturated cyclic hydrocarbon group, R 2 Preferably C2-C 10 Alkyl, 0<n≤4.

[0030] According to the catalyst component provided by the present invention, preferably, in the general formula (II), R 2 C2-C 10 The oxygen-containing titanium compound is preferably a titanate, more preferably at least one selected from tetrabutyl titanate, tetraethyl titanate, tetrapropyl titanate, tetraisopropyl titanate, and tetra-tert-butyl titanate.

[0031] According to a preferred technical solution of the present invention, the alcohol ether compound is selected from low-carbon alcohol ethers of ethylene glycol and / or propylene glycol, and the alcohol ether compound is selected from at least one of propylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether, ethylene glycol monopropyl ether, propylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monobutyl ether and propylene glycol monopropyl ether.

[0032] According to the preferred technical solution of the present invention, the ether compound is selected from at least one of anisole, phenethyl ether, propyl ether, butyl ether, isopropyl ether, isobutyl ether, 1,4-dioxane, tetrahydrofuran, ethylene oxide, 1,2-propylene oxide, 1,2-butylene oxide, cis-2,3-butylene oxide, trans-2,3-butylene oxide, 9,9-(bismethoxymethyl)fluorene, isopentyl ether and amyl ether, preferably a cyclic ether of 3-5 carbon atoms, such as tetrahydrofuran, methyltetrahydrofuran, preferably tetrahydrofuran. The molar ratio of cyclic ether / magnesium is 15-100, preferably 15-60.

[0033] According to the preferred technical solution of the present invention, the halogenating agent is of the general formula (III) R 3 a MX b As shown, wherein M is a third, fourth, or fifth group element or a transition metal element, X is a halogen, and R 3 C2-C 20 Saturated or unsaturated straight or branched chain hydrocarbon group, C3-C 20 Saturated or unsaturated cyclic hydrocarbon or alkoxy, C6-C 20 Aromatic group, a=0, 1, 2, b=1, 2, 3, 4.

[0034] According to the catalyst component provided by the present invention, preferably, in the general formula (III), M is selected from aluminum, silicon, R 3 C2-C 10 Saturated or unsaturated straight or branched chain hydrocarbon group, or C3-C 10 Saturated or unsaturated cyclic hydrocarbon group; the halogenating agent is preferably selected from R 4 P SiCl 4-P , R 5q-1 AlCl 4-q , wherein R 4 , R 5 is a C2-C 20 saturated or unsaturated straight-chain or branched hydrocarbon group, a C3-C 20 saturated or unsaturated cycloalkyl group or alkoxy group, a C6-C 20 aromatic group, p and q are integers, 0 ≤ p < 4, 0 < q < 4; the halogenating reagent is more preferably selected from at least one of diethylaluminum chloride, diethylaluminum monochloride, isobutylaluminum dichloride, diisobutylaluminum monochloride, isopropylaluminum dichloride, diisopropylaluminum monochloride, silicon tetrachloride, methyltrichlorosilane, ethyltrichlorosilane, propyltrichlorosilane, phenyltrichlorosilane. More preferably, (C2H5)AlCl2, isobutylaluminum dichloride, silicon tetrachloride, (C2H5O)AlCl2, (C6H5)AlCl2, (C6H5O)AlCl2, (C6H 12 O)AlCl2.

[0035] According to the preferred technical solution of the present invention, based on the total weight of the catalyst component, the content of the hexagonal mesoporous material carrier is 20-90% by weight, preferably 20-70% by weight; the magnesium component is calculated as magnesium element, and the content of the magnesium component is 1-50% by weight, preferably 1-30% by weight; the titanium component is calculated as titanium element, and the content of the titanium component is 1-50% by weight, preferably 1-15% by weight.

[0036] According to the preferred technical solution of the present invention, the average pore diameter of the catalyst component is 4-15 nm, the specific surface area is 450-500 m 2 / g, the pore volume is 0.5-1 mL / g, and the average particle size is 5-40 μm.

[0037] The second aspect of the present invention is to provide a method for preparing the catalyst component described in the first aspect, including: in the presence of a protective atmosphere, subjecting the at least one hexagonal mesoporous material carrier to a first contact reaction with the following raw materials: at least one magnesium compound, at least one oxygen-containing titanium compound, at least one alcohol ether compound, and at least one ether compound, and then subjecting it to a second contact reaction with a halogenating reagent to obtain a sprayable slurry, and then spray-drying the sprayable slurry to obtain the catalyst.

[0038] According to the present invention, the protective atmosphere can be nitrogen and / or inert gas.

[0039] According to the preferred technical solution of the present invention, the conditions of the first contact reaction include:

[0040] The temperature is 0-100 °C, and the reaction time is 0.1-10 h.

[0041] According to a preferred technical solution of the present invention, the conditions for the second contact reaction include: a temperature of 0-80° C. and a reaction time of 0.5-10 h.

[0042] According to the preferred technical solution of the present invention, the spray drying conditions include: carried out under a nitrogen protective atmosphere, an air inlet temperature of 100-200°C, an air outlet temperature of 60-130°C, and a carrier gas flow rate of 200-600L / h.

[0043] According to a preferred technical solution of the present invention, the amount of the hexagonal mesoporous material carrier is 60-220 g, preferably 80-180 g, and more preferably 90-160 g, relative to each mole of magnesium compound calculated as magnesium element; the amount of the oxygen-containing titanium compound is 0.1-20 moles, preferably 0.1-5.0 moles, and more preferably 0.1-3.0 moles; the amount of the alcohol ether compound is 0.1-10 moles, preferably 0.1-5.0 moles, and more preferably 0.1-3.0 moles; the amount of the ether compound is 0.01-100 moles, preferably 5-80 moles, and more preferably 15-60 moles; the amount of the halogenating agent is 0.1-50 moles, preferably 0.1-10 moles, and more preferably 0.1-5 moles.

[0044] According to a preferred technical solution of the present invention, the method for preparing the catalyst component comprises:

[0045] (1) contacting and reacting a magnesium compound, an oxygen-containing titanium compound, an alcohol ether compound and an ether compound to form a magnesium-titanium compound component solution;

[0046] (2) contacting the solution obtained in step (1) with the mesoporous material carrier to obtain a slurry;

[0047] (3) contacting the slurry obtained in step (2) with a halogenating agent to obtain a slurry to be sprayed;

[0048] (4) spray-drying the slurry to be sprayed obtained in step (3) to obtain the catalyst component for ethylene polymerization reaction.

[0049] According to the preferred specific embodiment of the present invention described above, in step (1), the magnesium compound, the oxygen-containing titanium compound, the alcohol ether compound and the ether compound are contacted and reacted at 30-100°C, preferably at 40-80°C. A higher temperature is beneficial to the reaction. The reaction is carried out under stirring. The reaction time depends on the properties of the reactants and the operating conditions. The reaction time is required to be sufficient to obtain a transparent solution. The required reaction time is 1-20 hours, preferably 2-10 hours. Until the reaction forms a transparent solution.

[0050] According to the preferred specific embodiment of the present invention described above, in step (2), the transparent solution obtained in step (1) is contacted with the mesoporous carrier for reaction at 0-100°C, preferably 0-80°C; the mixing time is generally selected from 30 minutes to 10 hours, preferably 0.5-4 hours.

[0051] According to the preferred specific embodiment of the present invention described above, step (1) and step (2) can be combined into a one-step reaction to simplify the preparation process.

[0052] According to the preferred specific embodiment of the present invention described above, step (3) is to contact the suspension obtained in step (2) with a halogenating agent for reaction, the reaction temperature is 0-80°C, preferably 20-70°C; the reaction time is 0.5-10h, preferably 0.5-5h, to obtain the masterbatch to be sprayed, in which the chlorination reaction or chlorination reduction reaction of the magnesium-titanium complex is completed, that is, the chlorine element replaces the alkoxy group in the magnesium-titanium complex, and different halogenating agents can also reduce the valence state of the oxygen-containing titanium compound to a lower valence state. The halogenation reaction usually controls the kettle temperature so as not to cause local overheating of the reaction, and stirring is usually performed during the feeding process to facilitate the smooth progress of the reaction. The reaction time can be 1 minute to 10 hours, preferably 0.5-5 hours.

[0053] According to the preferred specific embodiment of the present invention described above, in the step (4), according to a preferred embodiment of the present invention, the spray drying adopts an airflow spray drying method. The spray drying can be carried out in an atomizer. The conditions of the spray drying may include: being carried out under a nitrogen protective atmosphere, and the spray conditions include: an inlet temperature of 100 to 200°C, preferably 120 to 160°C; an outlet temperature of 60 to 130°C, preferably 90 to 115°C, and a carrier gas flow rate of 200-600L / h.

[0054] In the present invention, the polyolefin catalyst obtained by loading the magnesium component and / or the titanium component on the hexagonal mesoporous material carrier prepared by the above method has a spherical morphology, a higher loading amount of the magnesium component and / or the titanium component and a more reasonable pore structure. When used for the polymerization of olefin monomers, the polymerization activity is higher and the obtained polymer has a high bulk density.

[0055] The third aspect of the present invention is to provide a catalyst comprising the reaction product of the following components:

[0056] Component (A): the catalyst component described in the first aspect or the catalyst component obtained by the preparation method described in the second aspect;

[0057] Component (B): General formula (IV) AlR s X 3-sThe organoaluminum compound shown in the formula, wherein R is a hydrocarbon group having 1 to 20 carbon atoms or hydrogen, X is a halogen atom, s is an integer, 1 <s≤3。

[0058] Among them, component (B) can be selected from one or more alkyl aluminums, and the organic aluminum compound is preferably selected from AlEt3, Al(iso-Bu)3, Al(n-C6H 13 )3. Al(n-C8H 17 )3 and at least one of AlEt2Cl.

[0059] In the catalyst of the present invention, the molar ratio of aluminum in the organoaluminum compound to titanium in the catalyst component is the common aluminum-titanium ratio used in catalysts in the art, preferably 20-500, more preferably 30-300.

[0060] The fourth aspect of the present invention is to provide a method for preparing the catalyst described in the third aspect, comprising the steps of mixing and reacting the catalyst component (A) and the organic aluminum compound.

[0061] The component (A) and the component (B) can be used directly in the polymerization reaction, or can be mixed and reacted before being used in the polymerization reaction.

[0062] The fifth aspect of the present invention is to provide an application of the catalyst component described in the first aspect, or the catalyst component obtained by the preparation method described in the second aspect, or the catalyst described in the third aspect, or the catalyst prepared by the preparation method described in the fourth aspect in an ethylene polymerization reaction.

[0063] The catalyst of the present invention can be used in ethylene homopolymerization and copolymerization of ethylene and other α-olefins.

[0064] The polymerization reaction conditions are not particularly limited and may be the olefin polymerization conditions commonly used in the art.

[0065] The α-olefin may be one of propylene, butene, pentene, hexene, octene, and 4-methyl-1-pentene.

[0066] The inventors of the present invention discovered during their research on the preparation of polyolefins by polymerization of olefin monomers that the carrier in the polyolefin catalyst prepared by the method of the present invention has a special cubic-centered Im3m structure and a hexagonal pore structure, and thus has a larger pore size and a higher specific surface area, which can effectively increase the loading amount of the active component. Combined with the specific raw material composition of the present invention, "the catalyst component includes the reaction product of the following raw materials: at least one carrier, at least one magnesium compound, at least one oxygen-containing titanium compound, at least one alcohol ether compound, at least one ether compound and at least one halogenating agent", the obtained catalyst component improves the catalytic activity of the obtained polyolefin catalyst, and the obtained polyolefin product has a higher bulk density.

[0067] The invention has high catalytic activity when used for ethylene homopolymerization or copolymerization, and the prepared polymer powder has high bulk density. The active center mother liquid and the carrier do not need to be filtered before the mixed reaction, and the process is simple and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 is a SEM scanning electron microscope image of the microscopic morphology of the polyolefin catalyst prepared in Example 1;

[0069] Figure 2 This is a SEM scanning electron microscope image of the microscopic morphology of the polyolefin catalyst prepared in Comparative Example 1. DETAILED DESCRIPTION

[0070] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0071] As mentioned above, the first aspect of the present invention provides a method for preparing a polyolefin catalyst, the method comprising the following steps:

[0072] (a) mixing and contacting a template, potassium sulfate, an acid agent and tetraethyl orthosilicate, and crystallizing and filtering the obtained mixture to obtain a hexagonal mesoporous material raw powder having a cubic center Im3m structure;

[0073] (b) subjecting the raw powder of the hexagonal mesoporous material to a template release treatment, a heat activation treatment and a ball milling treatment in sequence to obtain a hexagonal mesoporous material carrier;

[0074] (c) In the presence of an inert gas, the hexagonal mesoporous material carrier is mixed with a solution of a magnesium-titanium compound component to react, and after sufficient reaction, the mixture is contacted with a halogenating agent to react to obtain a slurry to be sprayed, and then the slurry to be sprayed is spray-dried to obtain a catalyst.

[0075] The raw materials used in the specific implementation manner of the present invention are commercially available.

[0076] The present invention will be described in detail below through examples.

[0077] In the following examples and comparative examples, polyoxyethylene-polyoxypropylene-polyoxyethylene was purchased from Fuka Company under the trade name Synperonic F108, with a molecular formula of EO 132 PO 60 EO 132 , average molecular weight M n =14600.

[0078] Test method:

[0079] Catalyst morphology: measured on an SL-30 field emission environmental scanning electron microscope produced by FEI Company of the United States; catalyst particle size distribution: MASTERSIZE particle size distribution instrument, n-hexane is a dispersant, and the measurement range is 0.02-2000μm; X-ray diffraction analysis is carried out on an X-ray diffractometer of model D8Advance purchased from Bruker AXS Company of Germany; pore structure parameter analysis is carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics Company of the United States, and the specific surface area and pore volume of the sample are calculated using the BET method; the titanium content in the catalyst is measured by Spectrumlab752s UV-visible spectrophotometer; the magnesium content in the catalyst is measured by chemical titration; the melt index of polyolefin is measured by the method specified in ASTM D1238-99; bulk density: measured according to the ASTM D1895-69 method.

[0080] The spray drying was carried out on a B-290 spray dryer produced by Buchi, Switzerland.

[0081] This example is used to illustrate a polyolefin catalyst and a preparation method thereof.

[0082] Example 1

[0083] 1) Preparation of vector

[0084] 2g (1.4×10 -4 mol) template F108, 5.24g (0.03mol) K2SO4 and 60g 2mol / L hydrochloric acid solution were stirred at 38°C until F108 was completely dissolved;

[0085] Add 4.2 g (0.02 mol) of ethyl orthosilicate to the above solution, stir at 38°C for 15 min, and stand at 38°C for crystallization for 24 h;

[0086] Then, 100 g of deionized water was added to the mixed solution to dilute it, followed by filtering and washing with deionized water for 4 times, and then suction filtration was performed to obtain the hexagonal mesoporous material raw powder having a cubic center Im3m structure;

[0087] The hexagonal mesoporous material raw powder with a cube-centered Im3m structure obtained above was calcined at 400° C. for 10 hours to remove the template agent, thereby obtaining the hexagonal mesoporous material A1; the product after the template agent was removed was then calcined at 400° C. for 10 hours under the protection of nitrogen for thermal activation treatment to remove the hydroxyl group and residual moisture of the hexagonal mesoporous material, thereby obtaining the thermally activated hexagonal mesoporous material B1;

[0088] Take 10g of the above-mentioned heat-activated hexagonal mesoporous material B1 and put it into a 100ml ball mill, wherein the ball mill is made of polytetrafluoroethylene, the grinding balls are made of agate, the diameter of the grinding balls is 3-15mm, the number is 30, the rotation speed is 400r / min, and under nitrogen protection, the temperature in the ball mill is 25°C for 20h to obtain 10g of hexagonal mesoporous material carrier C1 with an average particle diameter of 0.8-8μm.

[0089] 2) Preparation of polyolefin catalyst

[0090] (1) Into a glass reactor equipped with a stirring device and purged with N2 and maintained in N2 atmosphere, 45 mmol of magnesium dichloride, 100 ml of tetrahydrofuran, 11 mmol of tetrabutyl titanate, and 9.8 mmol of ethylene glycol monobutyl ether were added in sequence, and then the temperature was raised to 70° C. and stirred to react until a transparent solution was formed;

[0091] (2) The transparent solution obtained in step (1) was cooled to 25° C., 6.0 g of the hexagonal mesoporous carrier C1 was added thereto, and the mixture was stirred at 50° C. for 2 hours to obtain a suspension;

[0092] (3) adding 13.5 ml of 30 wt% ethylaluminum dichloride solution to the suspension obtained in step (2) using a constant pressure dropper. After the addition is complete, stirring and reacting for 1 hour to obtain a slurry to be sprayed;

[0093] (4) Under N2 protection, the spray dryer air inlet temperature was controlled to be 140°C, the air outlet temperature was controlled to be 105°C, and the carrier gas flow rate was 360 L / h, and spray drying was performed to obtain a solid flowable powder polyolefin catalyst Cat-1.

[0094] Catalyst Evaluation:

[0095] 1L hexane, 1mmol triethylaluminum and 20mg of the above catalyst components were added to a 2L stainless steel stirred tank, and then the temperature was raised to 75°C, and 0.18MPa of hydrogen was added. After the hydrogenation was completed, 0.75MPa of ethylene was added, and the temperature was raised to 85°C for polymerization. After 2 hours of reaction, the addition of ethylene was stopped, the temperature was lowered, the pressure was released, the polyethylene powder was weighed, and the activity of the catalyst was calculated. The bulk density of the polyethylene powder was tested, and the polymerization results are shown in Table 3. The results of the catalyst scanning electron microscope test are shown in Figure 1 .

[0096] The hexagonal mesoporous material carrier C1 and polyolefin catalyst Cat-1 were characterized by XRD, TEM and nitrogen adsorption.

[0097] In the catalyst Cat-1 obtained in this example, the content of magnesium element is 6.89 wt % and the content of titanium element is 2.26 wt %, calculated as elements.

[0098] The hexagonal mesoporous material carrier C1 was subjected to X-ray diffraction spectrum detection, wherein the horizontal axis is 2θ and the vertical axis is intensity. It can be clearly seen from the XRD spectrum that the hexagonal mesoporous material carrier C1 has a diffraction peak of the (110) plane (2θ=0.6°) and a diffraction shoulder peak of the (200) plane (2θ=1.2°) in the small angle area that are consistent with the cube-centered Im3m. The diffraction peak of the (110) plane is high in intensity and narrow in shape, indicating that the hexagonal mesoporous material carrier C1 has a good long-range ordered structure, which is consistent with the XRD spectrum of the FDU-6 mesoporous material reported in the literature (Chengzhong Yu, Bozhi Tian, ​​Jie Fan, Galen D. Stucky, Dongyuan Zhao, J. Am. Chem. Soc. 2002, 124, 4556-4557). In addition, the position of the diffraction shoulder peak (2θ = 1.2°) of the (200) plane is completely different from that of the hexagonal or layered structure.

[0099] The nitrogen adsorption-desorption curve of the hexagonal mesoporous material carrier C1 (the horizontal axis is the relative pressure, the unit is p / p0), through the analysis of the pore size distribution diagram of the hexagonal mesoporous material carrier C1 (the horizontal axis is the pore size, the unit is 0.1nm), it can be seen from the pore size distribution diagram that the hexagonal mesoporous material carrier C1 has a narrow pore size distribution, and the pores are very uniform. The nitrogen adsorption-desorption isotherm shows that the hexagonal mesoporous material carrier C1 is a typical IUPAC-defined IV type adsorption-desorption isotherm, and the sample has an H2-type hysteresis loop, which proves that the hexagonal mesoporous material carrier C1 has a unique cubic cage-shaped mesoporous structure reported in the literature. The desorption branch between the relative partial pressure of 0.4-0.5 also shows that the material has a cage-like pore structure;

[0100] By examining the microscopic morphology of the hexagonal mesoporous material carrier C1 through TEM transmission electron microscope, the shape of the pores on the (100) crystal plane of the hexagonal mesoporous material carrier C1 can be clearly seen.

[0101] Figure 1 This is a SEM scanning electron microscope image of the microscopic morphology of the polyolefin catalyst Cat-1. As can be seen from the image, the microscopic morphology of the polyolefin catalyst Cat-1 is spherical and the particle size is at the micron level.

[0102] Table 1 shows the pore structure parameters of the hexagonal mesoporous material carrier C1 and the polyolefin catalyst Cat-1.

[0103] Table 1

[0104]

[0105] It can be seen from the data in Table 1 that after the magnesium component and the titanium component are loaded on the hexagonal mesoporous material carrier C1, the specific surface area and the pore volume are reduced, which indicates that the magnesium component and the titanium component enter the interior of the hexagonal mesoporous material carrier C1 during the loading reaction.

[0106] Example 2

[0107] This example is used to illustrate the polyolefin catalyst and the preparation method thereof of the present invention.

[0108] 1) Preparation of vector

[0109] 1.46 g (1 × 10 -4 mol) template F108, 6.96g (0.04mol) K2SO4 and 60g 2mol / L hydrochloric acid solution were stirred at 38°C until F108 was completely dissolved;

[0110] Add 3.1 g (0.015 mol) of ethyl orthosilicate to the above solution, stir at 38°C for 15 min, and stand at 40°C for crystallization for 20 h;

[0111] Then, 100 g of deionized water was added to the mixed solution to dilute it, followed by filtering and washing with deionized water for 4 times, and then suction filtration was performed to obtain the hexagonal mesoporous material raw powder having a cubic center Im3m structure;

[0112] The hexagonal mesoporous material raw powder with a cube-centered Im3m structure obtained above was calcined at 600° C. for 20 h to remove the template agent, thereby obtaining the hexagonal mesoporous material A2; the product after the template agent was removed was then calcined at 500° C. for 10 h under the protection of nitrogen for thermal activation treatment to remove the hydroxyl groups and residual moisture of the hexagonal mesoporous material, thereby obtaining the thermally activated hexagonal mesoporous material B2;

[0113] 10g of the above-mentioned heat-activated hexagonal mesoporous material B2 was put into a 100ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 3-15mm, the number was 30, and the rotation speed was 300r / min. Under nitrogen protection, the ball mill was milled at 30°C for 20h to obtain about 10g of hexagonal mesoporous material carrier C2 with an average particle diameter of 0.9-7μm.

[0114] 2) Preparation of polyolefin catalyst

[0115] The catalyst component was prepared according to the method of Example 1, except that the amount of hexagonal mesoporous carrier C2 was changed from 6.0 g to 4.5 g. The catalyst was numbered Cat-2. The catalyst was evaluated the same as in Example 1. The polymerization results are shown in Table 3.

[0116] The hexagonal mesoporous material carrier C2 and polyolefin catalyst Cat-2 were characterized by nitrogen adsorption instrument.

[0117] In the catalyst Cat-2 obtained in this example, the content of magnesium element is 8.4 wt % and the content of titanium element is 2.30 wt %, calculated as elements.

[0118] Table 2 shows the pore structure parameters of the hexagonal mesoporous material carrier C2 and the polyolefin catalyst Cat-2.

[0119] Table 2

[0120]

[0121] It can be seen from the data in Table 2 that after the magnesium component and the titanium component are loaded on the hexagonal mesoporous material carrier C2, the specific surface area and the pore volume are reduced, which indicates that the magnesium component and the titanium component enter the interior of the hexagonal mesoporous material carrier C2 during the loading reaction.

[0122] Example 3

[0123] The catalyst component was prepared according to the method of Example 1, except that 9.8 mmol of ethylene glycol monobutyl ether in the catalyst preparation step (1) was replaced by 9.8 mmol of propylene glycol monobutyl ether.

[0124] The evaluation of the catalyst was the same as in Example 1. The polymerization results are shown in Table 3.

[0125] Example 4

[0126] The catalyst component was prepared according to the method of Example 1, except that 11 mmol of tetrabutyl titanate in the catalyst preparation step (1) was replaced by 11 mmol of tetraethyl titanate.

[0127] The evaluation of the catalyst was the same as in Example 1. The polymerization results are shown in Table 3.

[0128] Example 5

[0129] The catalyst component was prepared according to the method of Example 1, except that 100 ml of tetrahydrofuran in the catalyst preparation step (1) was replaced by 130 ml of tetrahydrofuran. The catalyst was evaluated as in Example 1, and the polymerization results are shown in Table 3.

[0130] Example 6

[0131] The catalyst component was prepared according to the method of Example 1, except that 13.5 ml of 30 wt% ethylaluminum dichloride solution in the catalyst preparation step (3) was replaced by 2.8 ml of silicon tetrachloride. The catalyst was evaluated as in Example 1. The polymerization results are shown in Table 3.

[0132] Example 7

[0133] The catalyst component was prepared according to the method of Example 1, except that 9.8 mmol of ethylene glycol monobutyl ether in the catalyst preparation step (1) was replaced by 11 mmol of propylene glycol monomethyl ether. The catalyst was evaluated as in Example 1, and the polymerization results are shown in Table 3.

[0134] Comparative Example 1

[0135] (1) Into a glass reactor equipped with a stirring device and purged with N2 and maintained in N2 atmosphere, 45 mmol of magnesium dichloride, 120 ml of tetrahydrofuran, and 9.8 mmol of titanium tetrachloride were added in sequence, and the temperature was raised to 70°C and stirred to react until a transparent solution was formed.

[0136] (2) cooling the transparent solution obtained in step (1) to 50° C., adding 6.0 g of fumed hydrophobic silica (Cabot Corporation TS-610, particle size 0.02-0.1 μm) thereto, stirring and reacting for 2 hours to obtain a suspension;

[0137] (3) Under N2 protection, the spray dryer air inlet temperature was controlled to be 140°C, the air outlet temperature was controlled to be 105°C, and the carrier gas flow rate was 360 L / h, and spray drying was performed to obtain a solid flowable powder polyolefin catalyst.

[0138] The evaluation of the catalyst was the same as in Example 1. The polymerization results are shown in Table 3. The results of the catalyst scanning electron microscopy test are shown in Figure 2 .

[0139] Comparative Example 2

[0140] (1) Into a glass reactor equipped with a stirring device and purged with N2 and maintained in N2 atmosphere, 45 mmol of magnesium dichloride, 120 ml of tetrahydrofuran, 9.8 mmol of titanium tetrachloride, and 9.3 mmol of epichlorohydrin were added in sequence, and the temperature was raised to 70°C and stirred to react until a transparent solution was formed.

[0141] (2) cooling the transparent solution obtained in step (1) to 50° C., adding 5.6 g of fumed hydrophobic silica (Cabot Corporation TS-610, particle size 0.02-0.1 μm) thereto, stirring and reacting for 2 hours to obtain a suspension;

[0142] (3) Under N2 protection, the spray dryer air inlet temperature was controlled to be 140°C, the air outlet temperature was controlled to be 105°C, and the carrier gas flow rate was 360 L / h, and spray drying was performed to obtain a solid flowable powder polyolefin catalyst.

[0143] The evaluation of the catalyst was the same as in Example 1. The polymerization results are shown in Table 3.

[0144] Comparative Example 3

[0145] The preparation of the polyolefin catalyst was carried out according to the method of Example 1, except that, in step 2, when preparing the catalyst, 9.8 mmol of ethylene glycol monobutyl ether was not added. The evaluation of the catalyst was the same as in Example 1. The polymerization reaction results are shown in Table 3.

[0146] Table 3

[0147]

[0148] (Where: BD—Bulk Density)

[0149] It can be seen from the experimental data of the examples and comparative examples in Table 3 that the polymer bulk density is relatively high while the activity of the catalyst obtained by the present invention is maintained at a relatively high level. Figure 1 , Figure 2 It can be seen from the comparison that, compared with the comparative example catalyst, the particle shape of the catalyst of the present invention is spherical, the particles are uniform, the sphericity is good, and the dispersibility is good.

[0150] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

[0151] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.

[0152] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0153] The endpoints and any values ​​of the scope disclosed in the present application document are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, between the endpoint values ​​of each scope, between the endpoint values ​​of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be considered as specifically disclosed in this article.

[0154] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

[0155] Moreover, any embodiment described in this document may be freely combined with one or more other embodiments described in this document, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or original record of the present invention, and should not be regarded as new content that has not been disclosed or anticipated in this document, unless a person skilled in the art considers that the combination is obviously unreasonable.

Claims

1. A catalyst component comprising the reaction product of at least one support, at least one magnesium compound, at least one oxygen-containing titanium compound, at least one alcohol ether compound, at least one ether compound and at least one halogenating agent; The carrier is a hexagonal mesoporous material carrier, which has a cubic cage-like pore structure, a crystal structure with a cubic center Im3m structure, an average pore diameter of 4-15nm, and a specific surface area of ​​450-550m 2 / g, the pore volume is 0.5-1.5mL / g, and the average particle size is 0.5-10μm.

2. The catalyst component according to claim 1, characterized in that: The carrier is prepared by the following method: (a) mixing and contacting a template, potassium sulfate, an acid agent and tetraethyl orthosilicate, and crystallizing and filtering the obtained mixture to obtain a raw powder of a hexagonal mesoporous material; (b) subjecting the raw powder of the hexagonal mesoporous material to a template release treatment, a heat activation treatment and a ball milling treatment in sequence to obtain a hexagonal mesoporous material carrier.

3. The catalyst component according to claim 2, characterized in that: In step (a), the molar ratio of the template, potassium sulfate and tetraethyl orthosilicate is 1:100-800:20-200; and / or, The template agent is a triblock copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene; and / or, the acid agent is at least one of hydrochloric acid, sulfuric acid, nitric acid, and hydrobromic acid; More preferably, the mixed contact conditions include: temperature of 25-60°C, time of 10-240 min, pH value of 1-7; and / or, The crystallization conditions include: temperature of 25-60° C. and time of 10-72 h.

4. The catalyst component according to claim 2, characterized in that: In step (b), the process of the template release agent treatment includes: calcining the hexagonal mesoporous material raw powder at 300-600° C. for 8-20 hours; and / or, The conditions of the thermal activation treatment include: a thermal activation temperature of 300-900° C. and a thermal activation time of 7-10 h; and / or, The conditions of the ball milling treatment include: the rotation speed of the grinding balls is 300-500 r / min, and / or the temperature in the ball mill is 15-100° C., and / or the ball milling time is 0.1-100 h.

5. The catalyst component according to claim 1, characterized in that: The magnesium compound is of the general formula (I) Mg(OR 1 ) m Cl 2-m As shown, R 1 C2-C 20 Saturated or unsaturated straight or branched chain hydrocarbon group, or C3-C 20 Saturated or unsaturated cyclic hydrocarbon group, R 1 Preferably C2-C 10 alkyl; 0≤m≤2; and / or, The oxygen-containing titanium compound is of the general formula (II) Ti(OR 2 ) n Cl 4-n As shown, R 2 C2-C 20 Saturated or unsaturated straight or branched chain hydrocarbon group, or C3-C 20 Saturated or unsaturated cyclic hydrocarbon group, R 2 Preferably C2-C 10 An alkyl group, 0<n≤4; and / or, The alcohol ether compound is selected from low-carbon alcohol ethers of ethylene glycol and / or propylene glycol, preferably at least one selected from propylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether, ethylene glycol monopropyl ether, propylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monobutyl ether and propylene glycol monopropyl ether; and / or, The ether compound is selected from at least one of anisole, phenethyl ether, propyl ether, butyl ether, isopropyl ether, isobutyl ether, 1,4-dioxane, tetrahydrofuran, ethylene oxide, 1,2-propylene oxide, 1,2-butylene oxide, cis-2,3-butylene oxide, trans-2,3-butylene oxide, 9,9-(bismethoxymethyl)fluorene, isopentyl ether and amyl ether; and / or, The halogenating agent is of the general formula (III) R 3 a MX b As shown, wherein M is a third, fourth, or fifth group element or a transition metal element, X is a halogen, and R 3 C2-C 20 Saturated or unsaturated straight or branched chain hydrocarbon group, C3-C 20 Saturated or unsaturated cyclic hydrocarbon or alkoxy, C6-C 20 Aromatic group, a=0, 1 or 2, b=1, 2, 3 or 4.

6. The catalyst component according to any one of claims 1 to 5, characterized in that: Based on the total weight of the catalyst components, the content of the hexagonal mesoporous material carrier is 20-90% by weight, preferably 20-70% by weight; the magnesium component is calculated as magnesium element, and the content of the magnesium component is 1-50% by weight, preferably 1-30% by weight; the titanium component is calculated as titanium element, and the content of the titanium component is 1-50% by weight, preferably 1-15% by weight; and / or, The average pore size of the catalyst component is 4-15nm, and the specific surface area is 450-500m 2 / g, the pore volume is 0.5-1mL / g, and the average particle size is 5-40μm.

7. A method for preparing the catalyst component according to any one of claims 1 to 6, comprising In the presence of a protective atmosphere, the at least one hexagonal mesoporous material carrier is subjected to a first contact reaction with the following raw materials: at least one magnesium compound, at least one oxygen-containing titanium compound, at least one alcohol ether compound and at least one ether compound, and then is contacted with a halogenating agent for a second contact reaction to obtain a slurry to be sprayed, and then the slurry to be sprayed is spray-dried to obtain a catalyst.

8. The preparation method according to claim 7, characterized in that: The conditions for the first contact reaction include: The temperature is 0-100°C and the reaction time is 0.1-10h; and / or, The conditions for the second contact reaction include: The temperature is 0-80°C and the reaction time is 0.5-10h; and / or, The spray drying conditions include: being carried out under a nitrogen protective atmosphere, an air inlet temperature of 100-200° C., an air outlet temperature of 60-130° C., and a carrier gas flow rate of 200-600 L / h.

9. The preparation method according to claim 7 or 8, characterized in that: Relative to each mole of magnesium compound calculated as magnesium element, the amount of the hexagonal mesoporous material carrier is 60-220g, preferably 80-180g, and more preferably 90-160g; the amount of the oxygen-containing titanium compound is 0.1-20 moles, preferably 0.1-5.0 moles, and more preferably 0.1-3.0 moles; the amount of the alcohol ether compound is 0.1-10 moles, preferably 0.1-5.0 moles, and more preferably 0.1-3.0 moles; the amount of the ether compound is 0.01-100 moles, preferably 5-80 moles, and more preferably 15-60 moles; the amount of the halogenating agent is 0.1-50 moles, preferably 0.1-10 moles, and more preferably 0.1-5 moles.

10. A catalyst comprising the reaction product of: Component (A): the catalyst component according to any one of claims 1 to 6 or the catalyst component obtained by the preparation method according to any one of claims 7 to 9; Component (B): General formula (IV) AlR s X 3-s The organoaluminum compound shown in the formula, wherein R is a hydrocarbon group having 1 to 20 carbon atoms or hydrogen, X is a halogen atom, s is an integer, 1 <s≤3。 11. A method for preparing the catalyst according to claim 10, comprising the step of mixing and reacting the catalyst component (A) and the organoaluminum compound.

12. Use of the catalyst component according to any one of claims 1 to 6, or the catalyst component obtained by the preparation method according to any one of claims 7 to 9, or the catalyst according to claim 10, or the catalyst prepared by the preparation method according to claim 11 in ethylene polymerization; preferably, Application in ethylene homopolymerization or ethylene and α-olefin copolymerization.

Citation Information

Patent Citations

  • Catalyst component for ethylene polymerization reaction and preparation method thereof, and catalyst and application thereof

    CN112759685A

  • Polyolefin catalyst component containing mesoporous material, preparation method therefor and use thereof

    CN113166302A

  • Polyolefin catalyst as well as preparation method and application thereof

    CN116063592A

  • Polyolefin catalyst component containing mesoporous material, preparation method therefor and use thereof

    US20210380730A1